Microbial contamination of toothbrush heads: A comparative study between conventional plastic and bamboo toothbrush – An In vitro pilot study - Srishti Agarwal; Richik Chakraborty; Jayaditya Modak; Balaji Manohar; Kumudini Panigrahi; S Bhuvaneshwari (Advances in Human Biology, 2024)
Introduction: Toothbrushes are one of the most essential tools to maintain oral health. It has gone through several developmental phases. In ancient times, the brushes were made up of bamboo, but currently, we use nylon brushes. Bamboo brushes were thought to harbour more microorganisms. Hence, we undertook this study to evaluate and compare microbial contamination between plastic and bamboo toothbrush heads under different storage environments (room and washroom with attached toilet). Materials and Methods: Plastic and bamboo toothbrushes were divided into two equal groups (26 each), which were further subdivided equally (13 each) and placed in a room and a washroom with an attached toilet. All the toothbrushes were washed twice a day for 1 min and placed back. A toothbrush from each subgroup was then transported to a laboratory in a sterile condition. Microbiological evaluation of the toothbrush heads was carried out every week for up to 12 weeks. Results: The maximum bacterial growth was observed in bamboo-headed toothbrushes stored in the washroom with an attached toilet. This may be attributed to the build-up of water from bristles to the toothbrush head and the moist environment of the washroom, promoting microbial growth. The most common microorganisms observed in the samples included Escherichia coli, Klebsiella species, Pseudomonas species, Enterobacter species, Enterococcus species and Staphylococcus aureus. Conclusion: Microbial contamination of toothbrushes holds relevance not only for oral health but also for general health, especially in immunocompromised patients. This study demonstrates the need for improving toothbrush storage practices, as open storage either in washrooms with attached toilets harbours microorganisms.